A Guide to the Project Management Body of Knowledge (PMBOK® Guide) -- Eighth Edition and the Standard for Project Management. - PMI, Project Management Institute; ProQuest (firma) (Chicago : Project Management Institute, 2026)
A Guide to the Project Management Body of Knowledge  (PMBOK®   Guide) remains the premier resource for project professionals around the world.The Eighth Edition is the most evidence-based and community-driven revision to date, shaped by nearly 48,000 data points, global practitioner insights, and two rounds of public feedback.
X5.4 Refinement of Project Management Principles.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books